China Building Energy Use and Carbon Emission Yearbook 2021 A Roadmap to Carbon Neutrality by 2060 - Hu, Shan.; Jiang, Yi.; Yan, Da.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
Double carbon targets have been one of the most motivations and targets for China$1 (Bs social and economic development. Building is one of the most important sectors to achieve energy savings and emission reductions. This book focuses on China$1 (Bs building energy usage and CO2 emissions, discusses the status quo of China$1 (Bs building energy of four categories, their characteristics and technologies to improve energy efficiency and achieve zero-carbon emissions. Specifically, this book in 2021 discussed the pathways to achieve carbon neutrality targets for China$1 (Bs building sector. This book also analyzed the energy mix, energy intensity, and technology perspectives to implement energy and carbon targets in urban residential building areas. This book consists of large-scale survey data, monitoring data and case studies. The discussion on technologies and policies is supported by a variety of evidence and continuous research for more than ten years. The information, data and policy suggestions will interest readers all around the world who work in energy, climate change, engineering and building science areas.s
CHAPTER 1 Introduction -- CHAPTER 2 Carbon neutrality pathways for China's building sector -- CHAPTER 3 China's building energy use and GHG emissions -- CHAPTER 4 Urban residential buildings energy and emissions.
Keywords: Sustainable architecture; Sustainable Architecture/Green Buildings; Buildings -- Energy consumption -- China; Atmospheric carbon dioxide -- China; Sustainable buildings -- China